A Comparison of Absorption Inhibition and Absorption Elution Techniques for Detection of ABO Blood Groups in Saliva in Meitei Population: A Cross Sectional Study - Sungoh JDO, Wanio; Singh , K P; Devi , T M (Journal of Indian Academy of Forensic Medicine, 2023)
The ABO blood group system is the significant element for forensic serological examination of blood and body fluids. ABO blood groups  are the primary, most common, conspicuous, and easily detectable groups. These blood group specific antigens are abundantly present in  many other bodily secretions such as sweat, semen and even saliva. Many studies have detected the presence of ABO blood groups in  saliva by using both the absorption inhibition and absorption elution methods. This study of blood group ABO antigens in saliva was  carried out using both the techniques in a tertiary care centre in Imphal, Manipur. Using absorption elution method, out of the 90 secretors subjects, positive results were obtained in 82 (91.1%) subjects and using  absorption inhibition method, positive results were detected in 71 (78.9%) subjects. On statistical analysis, the mean age in completed  years of the participants is calculated as 22.12 years with a standard deviation of 3.04 years. Further, comparative analysis showed that the  positive rate of absorption elution is more than that of absorption inhibition. Therefore, absorption elution method remains an important  tool for determination of blood group of an individual from saliva and it is an aid in forensic identification and in solving medico-legal  cases.
Keywords: Blood group; Secretor status; Absorption inhibition technique; Absorption elution technique